EFFECT OF THE AGEING TEMPERATURE, AGEING TIME AND QUENCHING TEMPERATURE ON PRECIPITATION KINETICS IN Al-Mg-Si ALLOY - Fatima Z. Lemmadi; Abdelouahed Chala; Okba Belahssen; Said Benramache (Acta Metallurgica Slovaca, 2014)
In the present paper, we have studied the effect of ageing temperature, ageing time and quenching temperature on structural, microstructure and mechanical properties of Al-Mg-Si alloy. The ageing temperature used in this work was 300 °C pending time 24 and 48 h. The structural properties were investigated using X-ray diffraction; the microstructural evolution was investigated using optical, scanning and transmission electron microscopies and microhardness measurement for the mechanical properties. After various states of ageing, the Al-Mg-Si alloy shows significant changes in the microstructure and microhardness values. After ageing, the microstructure of the matrix consisted of a two solid solution of α–Al and β– Mg2Si phases precipitation. After two-step heat treatment (quenching and ageing), the microhardness value were decreased with comparing original sample, the alloy reveals high β discontinuous precipitates. After ageing at 300 °C of original sample, corresponding to the minimum value of microhardness, the volume fraction of the continuous precipitate becomes smaller. We found be that the best results have been obtained with the ageing at 300 °C pendinf time 48 hours in all steps.